Does Human Capital Endowment of Foreign Direct Investment Recipient Countries Really Matter? Evidence from Cross‐country Firm Level Data. Issue 3 (17th July 2013) - Bhaumik, Sumon Kumar; Dimova, Ralitza
Abstract The stylized literature on foreign direct investment (FDI) suggests that developing countries should invest in the human capital of their labor force in order to attract FDI. However, if educational quality in developing country is uncertain such that formal education is a noisy signal of human capital, it might be rational for multinational enterprises to focus more on job‐specific training than on formal education of the labor force. Using cross‐country data from the textiles and garments industry, we demonstrate that training indeed has a greater impact on firm efficiency in developing countries than formal education of the workforce.